Prevalence and Clinical Laboratory Features of Cryptosporidiosis in Children under 5 Years of Age: A Cross-Sectional Study of Hospital Cases of Acute Intestinal Infection - Elena G. Starikova; Natalia I. Schubina; Olga V. Voronkova; Yulia V. Kovshirina; Nikolai D. Yarovoy (Вопросы современной педиатрии)
Background. Cryptosporidium protozoa are the leading causative agent of diarrhea and cause of death in children under 5 years of age. The role of cryptosporidia in the development and course of acute intestinal infections (AII) in children in Russia remains unstudied. Objective. Our aim was to study the prevalence and clinical laboratory features of cryptosporidium-associated aII in children under 5 years of age. Methods. A cross-sectional study (conducted in March-June 2017) included children admitted to hospital with symptoms of AII (fever, loose watery stools, weakness, decreased appetite and/or vomiting) by the ambulance service. On admission, stool samples were collected from all patients. Cryptosporidium oocysts were determined by microscopic examination of faecal smears stained according to Tsil-Nielsen after preliminary concentration by a modified formalin-ether technique. The presence of intestinal pathogens was determined by a bacteriological technique and using a polymerase chain reaction. Results. The study included 107 children with AII (girls — 51%). Cryptosporidia were detected in 28 (26%) patients, in 93% of cases — together with bacterial and/or viral pathogens. The etiological structure of cryptosporidium-associated AII and AII in cryptosporidiosis negative children (n = 79) did not differ. On admission, children with cryptosporidium-associated AII had a higher blood leukocyte count — 13.0_109/L (9.2; 16.0) versus 8.3_109/L (6.1; 11.2) in children without cryptosporidiosis (p < 0.001). It has been also found that antibiotics were more often used in the treatment of children with cryptosporidium-associated AII — in 21 (75%) versus 39 (49%) in the comparison group (p = 0.026). Conclusion. Cryptosporidia are detected in every fourth child with AII under 5 years of age. Patients with cryptosporidia are distinguished by a higher level of blood leukocytes upon admission and a more frequent prescription of antibiotics than in the group of cryptosporidiosis negative patients.